The Implementation of Unity Values among Generation Z in Shaping Nationalism Character - Kencana, Narwastu Gita; Putri, Mas Fierna Janvierna Lusie (Universitas Pamulang, 2026)
Indonesia is a multicultural nation that faces major challenges in maintaining unity amidst its ethnic, religious, linguistic, and cultural diversity. The value of unity, as reflected in the national motto “Bhinneka Tunggal Ika” (Unity in Diversity), is a key foundation for national stability and integrity. Generation Z, born in the digital era, holds great potential in preserving national unity but is also vulnerable to the effects of globalization and social media, which can influence national identity. This study explores how the value of unity is implemented by Generation Z in shaping patriotic character. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation. Informants included a Civics teacher, the vice principal, and Grade IX.1 students at SMP PGRI 1 Ciputat. The data analysis followed open coding, axial coding, and selective coding to identify patterns of unity implementation and its impact. Findings show that Generation Z understands and applies the value of unity through tolerance, cooperation, and togetherness in school activities like flag ceremonies, class duties, P5 projects, and honoring national symbols. The study concludes that embedding unity values in education effectively fosters a sense of patriotism in Generation Z.